Analisis Perbandingan Pengalaman Pengguna Aplikasi Whatsapp dan Telegram menggunakan Kuesioner Mecue - Alim Muhammad; Buce Trias Hanggara; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
User experience is how a person feels when using a service, product, or system. On February 8, 2021, WhatsApp as one of the most widely used applications today offers new policies such as data sharing, data forwarding to Facebook, data limitations in 2016 and encryption systems. The Whatsapp application lost a lot of users and switched to other instant messengers such as Telegram which has almost the same function as WhatsApp. Based on the issues that occurred, the researcher wanted to analyze the differences in user experience of Telegram and WhatsApp application users by using the Mecue questionnaire. the questionnaire was distributed to 54 respondents who had met the predetermined criteria. In the Mecue questionnaire there are 5 modules and 10 indicators, namely Usefulness, usability, visual aesthetics, status, commitment, positive emotions, negative emotions, product loyalty, intention to use and overall evaluation. This study resulted in a comparison of the average value of each indicator of the two applications where the Whatsapp application had a higher value in all indicators except for the visual aesthetics indicator.